Controllable ZnO nanostructures evolution via synergistic pulsed laser ablation and hydrothermal methods - Abbas, Khaldoon N. (Elsevier Ltd, 2016)
We report the morphology-controlled ZnO nanostructures (ZNSs) evolution synthesized via a novel and facile technique at different growth times, where the pulse laser ablation in liquid (PLAL) is creatively combined with hydrothermal (H) method (hereafter called PLAL-H technique). Four types of ZNSs with varying sizes and shapes such as tapers, multipods, flowers, and hollow flowers are produced on Si substrate via PLAL-H technique. Furthermore, multipod- and flower-like ZNSs are grown using direct hydrothermal method to compare them with the one obtained via synergistic effects of PLAL-H method. This catalyst-free fabrication method is not only cost-effective but greatly useful for the rapid production of different quality of ZNSs at low temperature. ZNSs synthesized under prolonged growth time (60 min) exhibited structural deformation. Growth technique and time dependent morphology, structure, composition, and optical properties of these as-grown ZNSs are characterized using FESEM, X-ray diffraction, FTIR, photoluminescence, and UV–vis measurements. Synthesized ZNSs revealed excellent crystallinity and growth process dependent variation in the physical and optical features. The ZNSs growth mechanism is understood. Excellent features of the results demonstrate that this synergized new growth technique may constitute a basis for modifying the morphology, sizes, and optical properties of ZNSs in a controllable manner useful for diverse applications.